Optimized preparation of activated carbon from municipal sewage sludge and application to the adsorption of azo dye from aqueous solutions - Jung, Kyung-Won; Lee, Seon Yong; Lee, Young Jae (WILEY, 2019)
In this study, the conditions for preparation of active carbon from municipal sewage sludge (MSS) were optimized from application to the efficient removal of the azo dye, Acid Orange 7 (AO7), from aqueous solutions. To maximize the adsorption capacity (response variable) of the MSS-derived activated carbon (MSS-AC), a 3(k) Box-Behnken design based on response surface methodology was used to simultaneously optimize five important conditions (independent variables), that is, carbonizing temperature (400-600 degrees C), carbonizing time (0.5-2.0 h), impregnation ratio (1.0-3.5 g KOH/g MSS), activating temperature (600-800 degrees C), and activating time (0.5-2.0 h). The optimal conditions were established as carbonizing temperature: 509 degrees C, carbonizing time: 1.25 h, impregnation ratio: 2.3 g KOH/g MSS, activating temperature: 681 degrees C, and activating time: 1.21 h, with an overall desirability function of 0.991. Further, the effects of various key parameters (solution pH, ionic strength, adsorbent dosage, initial concentration, contact time, and temperature) on the adsorption of AO7 on the as-synthesized MSS-AC were elucidated through a series of batch experiments. Adsorption kinetics and isotherm studies revealed that the adsorption process is accurately described by the pseudo-second order and Sips models. The theoretical maximum adsorption capacity of AO7 was found to be similar to 1410 mg/g at 25 degrees C, which is superior to that of the other adsorbents reported to date. Additionally, the intraparticle diffusion model suggested that the adsorption was controlled by both external surface adsorption and intraparticle diffusion. Thermodynamic studies also suggested that the adsorption of AO7 by MASS-AC is exothermic and is governed by physisorption. (c) 2018 American Institute of Chemical Engineers Environ Prog, 38: S267-S276, 2019
Keywords: RESPONSE-SURFACE METHODOLOGY; ACID ORANGE 7; BASIC DYE; CATIONIC DYES; METHYL-ORANGE; COCONUT HUSK; REMOVAL; WASTE; EQUILIBRIUM; WATER